Pseudomigraine Pleocytosis Syndrome - J Gordon Millichap (Pediatric Neurology Briefs)
A series of 50 patients with a total of 164 episodes of pseudomigraine with temporary neurologic symptoms and CSF lymphocytic pleocytosis (PMP syndrome) is reported from the University Hospital Marques de Valdecilla, Santander, Spain.